Adherence to ARRIVE guidelines in animal research articles published in a National and International Pharmacology Journal - Hotwani, Jitendra H.; Deshmukh, Kiran R.; Mehta, Manthan N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study compares the adherence to Animal Research: Reporting of In Vivo Experiments (ARRIVE) guidelines in an Indian (IJP: Indian Journal of Pharmacology) and International journal (JPET: Journal of Pharmacology and Experimental Therapeutics). Methods: All original animal studies published in IJP and JPET between January 2014 and September 2015 were downloaded manually and 100 articles were randomly chosen from each journal and analyzed using the ARRIVE guidelines checklist and checked for adherence. Results: Most articles indicated the ethical statement (IJP- 96%, JPET- 98%). Steps taken to minimize effects of subjective bias in the study design were not mentioned in more than half the articles (IJP-50%, JPET-37%). Details of experimental animals were not adequately reported (IJP- 79%, JPET-68%). Details of animal housing (IJP-20%, JPET-39%) and husbandry (IJP-59%, JPET-51%) were poorly reported. Explanation of sample size calculation was mentioned in 2% and 1% articles in IJP and JPET. Statistical methods were well explained, yet the methods used to assess whether the data met the assumptions of the statistical approach was poorly reported. Conclusions: The present study demonstrates relatively suboptimal reporting standards in animal studies published in IJP and JPET. Adherence to ARRIVE guidelines can be improved.